Online Versus Offline: Which Networks Spur Protests? - Niklas Potrafke; Felix Roesel (Center for Economic Studies and ifo Institute (CESifo), 2022)
Does social media or offline social cohesion overcome collective action problems more effectively when both types of networks are prevalent? We investigate non-violent protests against a place-based economic reform in Austria—a country where one in two citizens uses Facebook but also one in two citizens is a member of a local club or civic organization. Our results show that protests spread more in places with strong offline networks as measured by real-life networks like village, folklore, or dialect clubs. We do not find that social media penetration intensifies local protests, a finding corroborated by microdata.
Keywords: D71; D72; Z20; 330; online and offline networks; social media; social cohesion; civic organizations; social capital; protest; economic reform; populism